2000
DOI: 10.1073/pnas.011446498
|View full text |Cite
|
Sign up to set email alerts
|

spr-2 , a suppressor of the egg-laying defect caused by loss of sel-12 presenilin in Caenorhabditis elegans , is a member of the SET protein subfamily

Abstract: Presenilin plays critical roles in the genesis of Alzheimer's disease and in LIN-12͞Notch signaling during development. Here, we describe a screen for genes that influence presenilin level or activity in Caenorhabditis elegans. We identified four spr (suppressor of presenilin) genes by reverting the egg-laying defective phenotype caused by a null allele of the sel-12 presenilin gene. We analyzed the spr-2 gene in some detail. We show that loss of spr-2 activity suppresses the egg-laying defective phenotype of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 41 publications
1
39
0
1
Order By: Relevance
“…We have previously reported that p21 Cip1 interacts with the SET protein, which was firstly identified as a CAN-fusion gene in an acute undifferentiated leukemia (von Lindern et al, 1992;Adachi et al, 1994). SET belongs to a family of proteins, which includes the yeast nucleosome assembly protein NAP-I (Kawase et al, 1996), MB20 (Shen et al, 2001), Cell Division Antigen-1 (Chai et al, 2001), nucleolar transforming growth factor-b1 target (Ozbun et al, 2001), supressor of presenilin-2 (Wen et al, 2000) and testis-specific protein Y-encoded (Vogel et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that p21 Cip1 interacts with the SET protein, which was firstly identified as a CAN-fusion gene in an acute undifferentiated leukemia (von Lindern et al, 1992;Adachi et al, 1994). SET belongs to a family of proteins, which includes the yeast nucleosome assembly protein NAP-I (Kawase et al, 1996), MB20 (Shen et al, 2001), Cell Division Antigen-1 (Chai et al, 2001), nucleolar transforming growth factor-b1 target (Ozbun et al, 2001), supressor of presenilin-2 (Wen et al, 2000) and testis-specific protein Y-encoded (Vogel et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Table S1 at http://dev.biologists.org/supplemental/). (Eimer et al, 2002b;Jarriault and Greenwald, 2002;Wen et al, 2000). Furthermore, 43% of all hop-1(lg1501)/dpy-5(e61) I; sel-12(ar171) spr-3(by108) animals with only one remaining copy of hop-1 and no functional sel-12 gene display an Egl phenotype (Table 3).…”
Section: Hop-1 Transcription Is Regulated By Spr-3 and Spr-4mentioning
confidence: 99%
“…It is possible that SPR-3 and SPR-4 may also function by recruiting conserved co-repressor complexes to the hop-1 locus. Three other Spr genes, spr-1, spr-2 and spr-5, encode proteins similar to components of known co-repressors (Eimer et al, 2002b;Jarriault and Greenwald, 2002;Wen et al, 2000). SPR-2 is a member of the Nucleosome Assembly Protein (NAP) family and is most similar to the human oncogene SET .…”
Section: Do Spr-3 and Spr-4 Perform A Conserved Function?mentioning
confidence: 99%
“…Six genes (spr-1-spr-5 and sel-10) have been identified that strongly suppress the sel-12 defects [9][10][11][12][13][14]. In the strongest suppressor mutations, the penetrance of sel-12 defects is reduced to less than 10% and in the spr-3 gene to almost 0% [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although spr-2 was the first spr gene to be cloned, how it suppresses sel-12 on a molecular level remains unknown [10]. Unlike sel-10 mutations, mutations in spr-2 have no obvious effects on lin-12 signaling [10].…”
Section: Introductionmentioning
confidence: 99%